Extracellular vesicle release in an experimental ventilator-induced lung injury porcine model - Niklas Larsson; Jonas Claesson; Stefan Lehtipalo; Annelie Behndig; Fariborz Mobarrez; Michael Haney (PLoS ONE, 2025)
Harmful effects of mechanical ventilation with large tidal volumes, volutrauma, may contribute much to diffuse acute lung injury. Extracellular vesicles have been noted in the context of vital organ injury. We hypothesized that extracellular vesicles from acutely injured lung can be found in both lung and blood. In a two-hit experimental porcine model, we tested if extracellular vesicles could be detected in bronchoalveolar lavage fluid and in plasma over a six-hour period of large tidal volume ventilation after surfactant depletion. After 2 hours of volutrauma, bronchoalveolar lavage fluid showed increased levels of extracellular vesicles containing nucleic acids (stained by SYTO 13) and those positive for both SYTO 13 and HMGB1. No such increase was detected in plasma at any timepoint during the six-hour experiments. This shows that nucleic acid-containing extracellular vesicles appear to be involved in progression of lung injury, possibly indicating cellular damage, but their potential to serve as diagnostic biomarkers of acute lung injury progression, based on plasma sampling, and in the very early phase, is not confirmed by these findings.